2011
DOI: 10.1017/s0022109011000068
|View full text |Cite
|
Sign up to set email alerts
|

Negative Hedging: Performance-Sensitive Debt and CEOs’ Equity Incentives

Abstract: We examine the relation between CEOs' equity incentives and their use of performance-sensitive debt contracts. These contracts require higher or lower interest payments when the borrower's performance deteriorates or improves, thereby increasing expected costs of financial distress while also making a firm riskier to the benefit of option holders. We find that managers whose compensation is more sensitive to stock price volatility choose steeper and more convex performance pricing schedules, while those with h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(7 citation statements)
references
References 50 publications
0
7
0
Order By: Relevance
“…Based on previous literature (Q. Cheng & Warfield, 2005; Tchistyi et al, 2011), equity incentive is also an important influence variable. Equity incentive plan (EQ_INC) can motivate CEO to promote R&D process (Miller et al,2002; Zahra et al, 2000).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on previous literature (Q. Cheng & Warfield, 2005; Tchistyi et al, 2011), equity incentive is also an important influence variable. Equity incentive plan (EQ_INC) can motivate CEO to promote R&D process (Miller et al,2002; Zahra et al, 2000).…”
Section: Methodsmentioning
confidence: 99%
“…Cheng & Warfield, 2005). The shareholding makes them more loyal to the company and exert more effort on the work (Tchistyi et al, 2011). The literature showed that compensation and equity incentive both had a significant positive impact on corporate financial performance.…”
Section: Literature Review and Research Hypothesismentioning
confidence: 99%
“…Tchistyi et al. (2011) find that CEOs’ equity incentives are related to the steepness and convexity of performance‐pricing provisions. Therefore, we include three variables that capture CEO equity incentives: (1) CEO Equity Compensation , measured as the ratio of the CEO's stock and option grants to her total compensation; (2) CEO Equity Ownership , defined as the CEO's stock and option holdings in shares divided by the firm's outstanding shares and (3) CEO Portfolio Sensitivity , defined as the change in the value of the CEO's option portfolio resulting from a 1% increase in the firm's annualized standard deviation of stock returns.…”
Section: Methodsmentioning
confidence: 99%
“…Our paper complements the literature on the relationship between CEO equity incentives and debt contracting. Prior studies have examined how equity‐based compensation and managerial ownership affect debt pricing (Bagnani et al., 1994; Brockman et al., 2015; Ortiz‐Molina, 2006; Tchistyi et al., 2011), debt maturity (Brockman et al., 2010; Datta et al., 2005), and loan syndicate structure (L. Chen, 2014). CEO equity incentives enhance the upside potential of risky investments for CEOs and encourage risk‐taking.…”
Section: Introductionmentioning
confidence: 99%
“…Awarding managers stock options, which go up in value as the volatility of the underlying asset goes up, has the potential to make managers more willing to take risks and make decisions that are more aligned with shareholder interests. Empirical studies including Rajgopal and Shevlin (2002), Knopf et al (2002), Coles et al (2006), Sanders and Hambrick (2007), Low (2009), Billett et al (2010, Tchistyi et al (2011), andGormley et al (2013) show that stock options compensation is linked to managerial risk taking. Our paper goes one step further by finding that in oligopoly competition, shareholders have an incentive to make managers more risk taking than themselvesmaking the managers risk seeking, rather than just risk neutral, to gain an advantage in oligopolistic competition.…”
Section: Introduction and Literature Reviewmentioning
confidence: 99%